Gambaran aritmia pada pasien penyakit jantung koroner di RSUP Prof. Dr. R. D. Kandou Manado periode 1 Januari 2015 – 31 Desember 2015 - Kalangi, Cathleen S.; Jim, Edmond L.; Joseph, Victor F.F. (Universitas Sam Ratulangi, 2016)
Abstract: Arrhythmia is an abnormal heart rhythm which refer to every disturbance in frequency, regularity, original location or electrical impulses conduction of the heart. Ischemic myocardium characterized by ionic and biochemical alterations creates an unstable electrical substrate capable of initiating and sustaining arrhythmias, meanwhile infarction creates areas of electrical inactivity and blocks conduction, which also promotes arrhythmogenesis. This study was aimed to obtain the description of arrhythmias in coronary artery disease patients at Prof. Dr. R. D. Kandou Hospital Manado from 1 January 2015 to 31 December 2015. This was a descriptive retrospective study. There were 101 data of patients with Coronary Artery Disease (CAD) associated with arrhythmia, as follows: 57 cases (56%) of Stable Angina Pectoris (SAP), 6 cases (6%) of Old Myocardial Infarction (OMI), 16 cases (16%) of Unstable Angina Pectoris (UAP), 20 cases (20%) of Non ST Segment Elevation Myocardial Infarction (NSTEMI), and 2 cases (2%) of ST Segment Elevation Myocardial Infarction (STEMI). The majority of cases were males (66%) and aged 51-60 years old (35%). There were 62 cases (41%) of CAD patients associated with arrhythmia that had hypertension as the highest risk factor and 19 cases (12%) for smoker as the lowest risk factor. The highest number of patients was Angina Pectoris Stabil (APS), and the dominant arrhythmia was Premature Ventricular Contraction (PVC).Keywords: description, arrhythmia, coronary artery diseaseÂ Abstrak: Aritmia merupakan gangguan irama jantung yang merujuk kepada setiap gangguan frekuensi, regularitas, lokasi asal atau konduksi impuls listrik jantung. Iskemik miokardium ditandai dengan perubahan ion dan biokimiawi, mengakibatkan aktivitas listrik yang tidak stabil yang memicu dan mempertahankan aritmia, dan infark menciptakan daerah aktif dan blok konduksi listrik, yang juga memromosikan aritmogenesis. Penelitian ini bertujuan untuk mengetahui gambaran aritmia pada pasien penyakit jantung koroner (PJK) di RSUP Prof. Dr. R. D. Kandou Manado periode 1 Januari 2015-31 Desember 2015. Jenis penelitian ialah deskriptif retrospektif. Hasil penelitian mendapatkan 101 data pasien PJK yang mengalami aritmia, diantaranya Angina Pektoris Stabil (APS) 57 kasus (56%), Old Myocardial Infarction (OMI) 6 kasus (6%), Unstable Angina Pectoris (UAP) 16 kasus (16%), Non ST Segment Elevation Myocardial Infarction (NSTEMI) 20 kasus (20%), dan ST Segment Elevation Myocardial Infarction (STEMI) 2 kasus (2%). Mayoritas kasus ialah jenis kelamin laki-laki (66%), usia 51-60 tahun (35%). Faktor risiko tertinggi pada pasien PJK dengan aritmia ialah hipertensi (41%) dan terendah ialah merokok (12%). Kasus tertinggi ialah APS, dengan aritmia terbanyak ialah Premature Ventricular Contraction (PVC), Kata kunci: gambaran, aritmia, penyakit jantung koroner